The religious crisis of the 1960s - McLeod, Hugh (Oxford University Press, 2007)
The 1960s were a time of explosive change and innovation in the Christian churches, as well as of charismatic leaders like Pope John XXIII and Martin Luther King. Using oral history, Hugh McLeod explains what happened to religion in the 1960s, why it happened, and how the events of that decade shaped the rest of the 20th century.